Correlation of knowledge of balanced nutrition and eating patterns with biology learning outcomes through students' physical activity - Siti Zulfaidah Warli; A. Mushawwir Taiyeb; Syamsiah Syamsiah (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Insufficient nutritional knowledge, diets that do not meet nutritional adequacy levels, and excessive physical activity for the body affect the learning outcomes of some students. This study aims to investigate the relationship between knowledge about balanced nutrition and diet with biology learning outcomes through physical activity. This study is an ex post facto, which is correlational in knowing the relationship between knowledge of balanced nutrition and diet with biology learning outcomes through physical activity. The population in this study were all students of class XI of State Senior High School in Polewali Sub-district, Polewali Mandar Regency, 2023/2024 school year, which includes SMAN 1 Polewali, SMAN 2 Polewali, SMAN 3 Polewali and SMAN 4 Polewali. The sample in this study was taken as many as 210 using simple random sampling. The research instruments used in this study were a balanced nutrition knowledge test, a dietary pattern questionnaire in the form of a Food Frequency Questionnaire (FFQ) form, and a Global Physical Activity Questionnaire (GPAQ) physical activity questionnaire. The data obtained in this study were analyzed using descriptive statistical analysis and inferential path analysis with the help of the SPSS program. The results showed that knowledge of balanced nutrition with diet can affect biology learning outcomes, and diet with physical activity can affect biology learning outcomes. This research can impact the improvement of the health and wellbeing of learners by improving concentration and overall performance. It can assist in developing more effective educational strategies to promote health and academic achievement.Abstrak. Pengetahuan gizi yang kurang, pola makan yang tidak sesuai dengan tingkat kecukupan gizi, dan  aktivitas fisik yang berlebihan untuk tubuh mempengaruhi hasil belajar beberapa peserta didik. Penelitian ini bertujuan untuk menyelidiki hubungan antara pengetahuan tentang gizi seimbang dan pola makan dengan hasil belajar biologi melalui aktivitas fisik. Penelitian ini adalah ex post facto yang bersifat korelasional dengan tujuan untuk mengetahui hubungan pengetahuan gizi seimbang dan pola makan dengan hasil belajar biologi melalui aktivitas fisik. Populasi dalam penelitian ini adalah seluruh peserta didik kelas XI SMA Negeri se-Kecamatan Polewali, Kabupaten Polewali Mandar, tahun ajaran 2023/2024 yang meliputi SMAN 1 Polewali, SMAN 2 Polewali, SMAN 3 Polewali dan SMAN 4 Polewali. Sampel dalam penelitian ini diambil sebanyak 210 dengan menggunakan teknik simple random sampling. Instrumen penelitian yang digunakan dalam penelitian ini berupa tes soal pengetahuan gizi seimbang, kuisioner pola makan berupa formulir Food Frequency Questionnaire (FFQ), dan kuisioner aktivitas fisik Global Physical Activity Questonnaire (GPAQ). Data yang diperoleh dalam penelitian ini dianalisis menggunakan analisis statistik deskriptif dan inferensial analisis jalur (path analysis) dengan bantuan program SPSS. Hasil penelitian menunjukkan bahwa pengetahuan gizi seimbang dengan pola makan dapat mempengaruhi hasil belajar Biologi dan pola makan dengan aktivitas fisik dapat mempengaruhi hasil belajar Biologi dalam pembelajaran. Penelitian ini dapat berdampak terhadap peningkatan kesehatan dan kesejahteraan peserta didik untuk meningkatkan konsentrasi serta kinerja secara keseluruhan. Ini dapat membantu dalam pengembangan strategi Pendidikan yang lebih efektif untuk mempromosikan kesehatan dan prestasi dalam bidang akademik.